LINGUISTIC AND CULTURAL ADAPTATION OF FOREIGN STUDENTS AT THE UNIVERSITY OF CALIFORNIA, LOS ANGELES, UCLA - Yaroslav S. Slutskiy (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article analyzes the linguistic and socio-cultural adaptation training of foreign students at the University of California, Los Angeles, UCLA (USA). It was determined, that acculturation consists of two main components: linguistic and sociocultural. It has been reported that programs for improving the level of proficiency in a foreign (English) language for students from other countries should include a certain preparatory complex, the main components of which are reading, writing, listening, speaking, studying grammatical structures and increasing vocabulary, which will allow, firstly, to construct one’s own thoughts in the form of sentences during the interpersonal communication interaction, taking into account the grammatical rules. Secondly, it will form the ability to communicate on topics of an arbitrary type. The essence of elective courses aimed at the possibility of more branched communication using the idiomatic expressions, slang constructions, American pronunciation, etc. is considered. An important role in the foreign students’ language training played the involvement of consultants into the adaptation process who speak the native language of a foreign student, which allows to minimize the cross-cultural gap and more quickly establish the interpersonal contact, subsequently conducting bilingual classes, which also contribute to the development of preparatory activities «within society», when a foreign student gets the opportunity to perform the practical communication, using among other things, the native language, which ensures a faster acculturation process. Thus, after comparing the courses «Language Exchange» and «English Language Circle», it was revealed that the first is more effective in the development of communication skills due to the fact that it offers the communication with a native speaker, by the way, the conducting bilingual interaction. It was found that the socio-cultural component of the preparatory process is an important component of high-quality communication. The analyzed experience of the programs of the University of California made it possible to come to the conclusion about the significant role of familiarizing a foreign student with the cultural characteristics of the host country by conducting excursions, researching the socially significant areas that influence the American society (media, sport, cinema, etc.). That is why, the linguistic system of the University of California, Los Angeles is represented by the programs and courses of the intensive English. For the practical consolidation of theoretical material, the format of «within society» is actively adopted, which is characterized by the communicative contact with other personalities who are represented by both student and representatives of local community. Because of that the immersion approach is implemented. Further research of this problem should cover the level of linguistic and cultural adaptation training of foreign students in other higher educational institutions of the United States of America and other states with a high level of attendance of students from other countries; as well as conducting the comparative studies between the foreign and domestic experience of foreign students’ adaptation.